2014
DOI: 10.1002/adsc.201400631
|View full text |Cite
|
Sign up to set email alerts
|

N‐Imide Ylide‐Based Reactions: CH Functionalization, Nucleophilic Addition and Cycloaddition

Abstract: As valuable building blocks for introducing nitrogen, N-imide ylides represent an important class of reactive species and are synthons for the synthesis of nitrogen-containing heterocycles that potentially have biological activities. During the past decades, tremendous efforts have been devoted to the tandem processes involving N-imide ylides as well as their asymmetric applications. In particular, several types of N-imide ylide-based reactions have been established, such as C À H functionalization, nucleophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(22 citation statements)
references
References 144 publications
(69 reference statements)
0
22
0
Order By: Relevance
“…Aldehyde-derived N,N'-cyclic azomethine imines [(AE)-1i-l]showed high reactivity towards the reduction compared to the fluorenone-derived substrates, thus requiring lower catalyst loading and temperatures ( Table 2). These kinetic resolutions proceeded selectively at 40-60 8 8Ct op rovide enantioenriched azomethine imines (1i-l)a nd pyrazolidinones (2i-l)i nh igh yields (entries [1][2][3][4][5]. In addition to solving the lack of reactivity observed with some of the substrates in Table 1, this protocol allowed us to assign the absolute configuration of the products (resolved 1i was compared to previous reports).…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Aldehyde-derived N,N'-cyclic azomethine imines [(AE)-1i-l]showed high reactivity towards the reduction compared to the fluorenone-derived substrates, thus requiring lower catalyst loading and temperatures ( Table 2). These kinetic resolutions proceeded selectively at 40-60 8 8Ct op rovide enantioenriched azomethine imines (1i-l)a nd pyrazolidinones (2i-l)i nh igh yields (entries [1][2][3][4][5]. In addition to solving the lack of reactivity observed with some of the substrates in Table 1, this protocol allowed us to assign the absolute configuration of the products (resolved 1i was compared to previous reports).…”
Section: Methodsmentioning
confidence: 98%
“…Inthe past decade,a zomethine imines have been intensely studied in the field of asymmetric catalysis.T hese versatile compounds are well known as substrates in 1,3-dipolar cycloadditions and nucleophilic additions,aswell as directing groups and bifunctional catalysts. [1] In 2003, Shintani and Fu reported the first example of asymmetric catalysis with azomethine imines,where they described the enantioselective cycloaddition of prochiral N,N'-cyclic azomethine imines. [2] Since this report, there have been many examples of catalytic stereoselective reactions with N,N'-cyclic azomethine imines (1;see Scheme 1), [3] thus establishing their value as precursors to pyrazolidinones,h ydrazines,a nd b-aminocarbonyl compounds.H owever,b ecause of the difficult synthesis of structurally diverse azomethine imines,t he scope of these reactions is limited to simple and achiral substrates.W hile simple azomethine imines can be synthesized by the condensation of pyrazolidinones onto aldehydes,t he complex and ketone-derived 1 are typically inaccessible.…”
mentioning
confidence: 99%
“…1-Aminopyridiniums alt (1a) is ac ommercially availablec hemical, derivatives of which are usually used as building blocks for N-containing heterocycles. [9] Its primary-amine moiety can be modified and tuned through reactions with acid chloride or acid anhydride. In fact, various N-protected 1-aminopyridium salts (1b-e) [10] were prepared from 1a (Scheme 2) and they turned out to be shelf-stable chemicals.…”
mentioning
confidence: 99%
“…The structure of this compound was identified by X-ray crystallographya nalysis (see the Supporting Information). As imilar result was obtained upon using 1,1'-bis(diphenylphosphino)ferrocene (dppf) as ar eplacement ( [11][12][13][14][15], and it was found that no better yield was observed.W en ext examined the effect of the palladium catalyst in the transformation (Table1,e ntries 16-20). It seemed that palladium acetate was the most effective.…”
Section: Resultsmentioning
confidence: 80%
“…[3] The process can also follow another route (Scheme 1, path c), which would proceed through insertion of the triple bond of 2-alkynylaniline 1 to provide intermediate C.F urther carbometalation would give rise to intermediate D. b-Elimination with cleavage of the CÀCb ond [10] would produce intermediate E,w hich could then undergo intramolecular nucleophilic attack to generate polycyclic 7,8-dihydrobenzo[b]naphtho[2,3-d]azocin-6(5 H)-one 3.G iven that the selectivity of double carbometalation is excellent, we believed that the challenges of the competitive pathways could be addressed with judiciousc hoice of the reactionc onditions. Consistent with our continuing interesti nt he preparation of natural product like compounds, [11] we therefore startedt oi nvestigatet he practicability of the proposed palladium-catalyzed reaction of 2-alkynylanilines 1 with 2-(2-bromobenzylidene)cyclobutanones 2.…”
Section: Introductionmentioning
confidence: 90%